Revenue policy features as an important direction of social policy - M. A. Biganova (Управление)
The main provisions, essence and content of the revenue policy as a key part of the social policy of the state have been considered in the article. The author rightly notes, that the income policy is aimed at solving such important tasks as helping vulnerable groups of the population by resorting to the use of the social security system and leveling the inflationary processes that affect the income and savings of citizens. Various models of social regulation have been adduced, including the “Scandinavian” or “Swedish” model, monetarist, paternalistic, and others. The study have used various general scientific research methods: observation method, the systemic-functional method, method of synthesis and analysis, method of scientific abstraction.The main directions of improving the implementation of the state social policy, which is presented as a voluminous, multi-faceted process that has a complex structure and intersects with many other areas of state activity, have been proposed. The conclusion has been formulated, that society does not exist by itself, so the social sphere is in constant interaction with other spheres, such as production of material goods, politics, culture and the environment. It has been noted, that social policy is recognized as effective when the entire social sphere is at a high level, and the society clearly shows a positive response to the actions of the state. Thus, the broader is such a policy, the greater is the completeness of the covered areas, both explicit (the fight against poverty, social protection, etc.) and implicit (relations between social groups, motivation in society, etc.), the more effective is the overall functioning of the state as a whole.